Teacher-student and parent-child relationships as determinants of academic achievement in senior secondary school commerce in Ibadan, Oyo state (2011)
The study investigated the influence of teacher-student relationship and parent-child relationship on students' academic performance in senior secondary school commerce in Akinyele local government council area of Oyo state, Nigeria.Six schools were selected, making a total sample size of 250. Teacher-Student and Parent-Child Relationship Scale (TSPCRS) and students raw examination score records in commerce were the instruments that were employed to gather data for the study. Correlation and multiple regression statistics were used in analysing the data. Result showed that both of teacher-student and parent-child relationship had influence on students' performance in senior school commerce.